EP-215 COVID-19: Influence on Stoma Outcomes & Post-Operative Mortality. (9th August 2022) - Mactier, Mhairi; Tallo, Tracey; Robertson, Isobel; MacDonald, Angus
Abstract: Introduction: The COVID-19 pandemic resulted in cessation of elective surgery and a shift towards emergency surgery, often non-curative with stoma formation. Our hospital stoma database scores surgical complications (retraction, prolapse, stenosis and hernia) and patient symptoms (leakage, soiling, skin changes and odour), recorded by the specialist nurse at varying post-operative points. Aim: To compare stoma scores and post-operative mortality pre- and mid-pandemic. Methods: The stoma database (Microsoft Access) was interrogated for two periods: 16/03/19–16/09/19 (pre-pandemic) and 16/03/20–16/09/20 (mid-pandemic). Mortality at 6 and 12 months was extracted from electronic patient records (Clinical Portal). Results: Pre-pandemic, 28 patients underwent stoma formation. Median stoma score at post-operative day 3, day 10, 6 months and 12 months was 0(0–4), 0(0–4), 1(0–8) and 1(0–3) respectively. Post-operative mortality was 21% at 6 months and 36% at 12 months. Mid-pandemic, 19 patients underwent stoma formation. Median stoma score at equivalent time intervals was 0(0–2), 1(0–8), 0(0–5) and 4 (n=1 patient score recorded). There was a relative paucity of data recorded mid-pandemic with a maximum of 9 patient scores recorded at any one time. Post-operative mortality was 16% at 6 months and 26% at 12 months. Conclusions: While acute surgery during the pandemic does not appear to be associated with increased stoma complications and post-operative mortality was less during the pandemic, limited data recording makes true comparison of pre- and mid-pandemic stoma outcomes difficult. Assessing the impact of the COVID-19 pandemic on surgical outcomes may be limited by poor quality of data collected.